Pengujian IaC Berbasis DevOps dan Ansible Menggunakan Metode Black Box Testing - I Putu Agus Eka Pratama; Putu Bayu Suarnata Wahyu Putra (Faktor Exacta, 2022)
The development of information technology, which is followed by an increase in the need for devices and computing resources for services on computer networks, requires cost and time for the configuration and development process. Infrastructure as Code (IaC) based on DevOps using Ansible, is a solution to this problem, by combining development and operational processes. However, post-implementation, it is necessary to test on the application side to determine the functionality of the running system. For this reason, in this research, a Black Box Testing method with three steps is proposed for testing the implementation of DevOps-based IaC using Ansible. The test results show that the implementation of Ansible for DevOps-based IaC was successfully carried out by configuring the host node and running the Ansible playbook from the host server.